Fatale Traditionen = Fatal traditions - Klein, Wolfgang (Zeitschrift für Literaturwissenschaft und Linguistik, 2017)
Research lives on the accumulated knowledge and insights of earlier generations. But our way to deal with this heritage is peculiar and sometimes fatal. The history of science is full of legends, and it is often much more characterised by the glorification of the heroic deeds of a few geniuses than by an accurate picture of how knowledge evolved. Newton, Darwin and Einstein are perfect illustrations. At the same time, substantial progress in some disciplines is seriously hampered by concepts inherited from our scientific ancestors. The study of language, for example, is still based with notions such as ›subject, object, verb, noun‹. These notions were originally developed in the Antiquity for languages such as Greek and Latin, and they are adapted to their specific structural properties. But they have never found a precise definition. It is just this vagueness which makes them so perfectly suited for a first and rapid analysis of linguistic facts but which proves to be a serious obstacle to any deeper understanding of language.
Gesehen am 23.12.2020